High-level airport assessment of noise and carbon emissions trade-off for novel aircraft - a holistic approach to decision making - Stevens, Joy; Maldonado, Ana Luisa; Proenca, Anderson R. (American Institute of Aeronautics and Astronautics (AIAA), 2025)
As aviation demand grows, controlling carbon emissions is crucial for meeting 2050 net-zero targets. Complaints relating to airport noise have increased over recent years despite individual aircraft noise levels decreasing. Current aircraft designs face competing requirements to reduce fuel-burn or noise. To date, no existing high-level tools exist that determine the trade-offs between these two aircraft emissions at an individual aircraft or airport fleet level. This paper extends Powell's (2003) methodology, scaling the procedure for individual aircraft operations to enable a fleet-level assessment and allowing the impact of novel aircraft to be determined. The results of linear regression analysis were reproduced in AEDT (where Powell used INM) and included additional aircraft, such as business jets and propeller planes, to improve the accuracy for smaller, regional airports. A case study has been run for a UK airport with assumed noise levels of future aircraft based on Sustainable Aviation guidance, to demonstrate the change in noise and CO2 levels when introducing novel aircraft to the fleet. This has shown that the noise contour area increases when introducing novel hydrogen and electric aircraft compared to future low-noise technology designs with conventional propulsion mechanisms. The CO2 emissions were shown to decrease substantially when introducing novel hydrogen and electric aircraft, but increase for future low-noise technology designs with conventional propulsion mechanisms. This highlights the trade-offs between noise and CO2 and indicates that careful consideration must be given to future aircraft designs and fleet mixes if both emissions are to be reduced simultaneously.
Keywords: 38 Economics; 40 Engineering; 4001 Aerospace Engineering; 13 Climate Action